Oxygen chloride solid electrolyte as well as preparation method and application thereof

By adopting the chemical formula xLi2O-(1-y)ZrCl4-yAlCl3 of oxychloride solid electrolyte, and preparing it by high-energy ball milling method, the existing inorganic solid electrolyte cannot meet the problems of low Young's modulus, high ionic conductivity and low cost at the same time, achieving the excellent electrochemical performance and cost-effectiveness of all-solid lithium batteries.

CN119542517AActive Publication Date: 2025-02-28UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202411948824.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing inorganic solid electrolytes cannot meet the requirements of low Young's modulus, high ionic conductivity and low cost at the same time, resulting in limited application in all-solid lithium batteries.

Method used

The chemical formula of the oxychloride solid electrolyte is xLi2O-(1-y)ZrCl4-yAlCl3, and is prepared by high-energy ball milling method to ensure that the electrolyte is composed of amorphous phase and a low proportion of crystal phase, with a proportion of crystal phase accounting for ≤20%, so as to achieve low Young's modulus and high ionic conductivity.

Benefits of technology

The Young's modulus of oxychloride solid electrolyte is lower than 4GPa and the ionic conductivity is higher than 1mS·cm-1, and does not require expensive raw materials, with significant cost advantages and good commercial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542517A_ABST
    Figure CN119542517A_ABST
Patent Text Reader

Abstract

The invention provides an oxychloride solid electrolyte as well as a preparation method and application thereof, and belongs to the technical field of all-solid-state lithium battery materials. The chemical general formula of the oxychloride solid electrolyte disclosed by the invention is xLi2O-(1-y) ZrCl4-yAlCl3, wherein 0 lt; x is less than or equal to 3, 0lt; y < = 1. Compared with other solid electrolytes such as sulfides, halides, oxides and the like (the Young modulus mostly exceeds 20 GPa and even is higher than 100 GPa), the oxygen chloride solid electrolyte has lower Young modulus (not higher than 4 GPa); the all-solid-state lithium battery assembled by using the oxychloride solid electrolyte disclosed by the invention has excellent surface capacity and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state lithium battery materials, and in particular to an oxychloride solid electrolyte and a preparation method and application thereof. Background Art

[0002] As the next generation of energy storage technology, the application of all-solid-state lithium batteries is expected to solve the inherent safety and energy density problems of traditional lithium-ion batteries. As a key component of solid-state batteries, there is currently no single solid electrolyte that can meet all the necessary requirements for commercial applications, including high ionic conductivity, good mechanical deformation ability, and cost-effectiveness. Due to the lack of these key properties, previously reported inorganic solid electrolytes have challenges such as slow ion transport efficiency, poor electrode interface contact, and high production costs, which seriously hinder their practical application in all-solid-state lithium batteries.

[0003] Unlike traditional lithium-ion batteries, where liquid electrolytes can easily penetrate into the electrodes to provide sufficient ionic conductivity, solid-state batteries must rely on solid-solid contact of electrolyte particles to establish an ion percolation network within the electrodes. In order to form good solid-solid contact with brittle commercial positive electrode active material particles such as high-nickel ternary oxides and lithium iron phosphate under pressure, solid electrolytes need to have as low a Young's modulus as possible. However, as brittle materials, the Young's modulus of oxide electrolytes generally exceeds 100 GPa (for example, Li 0.33 La 0.56 TiO3: ~200GPa; Li7La3Zr2O 12 :~156GPa;Li 1.5 Al 0.5 Ge 1.5 P3O 12 :~115GPa), which cannot meet this requirement. In contrast, although sulfides and chlorides have certain machinability, their mechanical properties are still unsatisfactory. For example, the representative sulfide electrolytes Li6PS5Cl and Li 10 GeP2S 12 The Young's modulus of the representative chloride electrolytes Li3YCl6, Li2ZrCl6 and Li3InCl6 are 45.75GPa, 22.5GPa and 19.8GPa respectively. However, in order to achieve good solid-solid contact, the solid electrolyte needs to have a Young's modulus below 10GPa (ACS Appl.Energy Mater.2023,6,9615-9623). In addition to the extremely low Young's modulus, the solid electrolyte also needs to have a sufficiently high ionic conductivity (higher than 1mS·cm at 25°C). -1), and expensive compounds such as Li2S and rare earth chlorides cannot be used as raw materials (otherwise they will not be commercialized due to high costs). However, there are currently no inorganic solid electrolytes that can meet the above requirements at the same time, especially solid electrolytes with a Young's modulus below 10GPa are particularly rare.

[0004] Therefore, it is very important to provide an oxychloride solid electrolyte with extremely low Young's modulus, high ionic conductivity and low cost. Summary of the invention

[0005] The object of the present invention is to provide an oxychloride solid electrolyte and a preparation method and application thereof, so as to solve the technical problem in the prior art that both low Young's modulus and high ionic conductivity cannot be satisfied and the preparation cost is high.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides an oxychloride solid electrolyte, wherein the chemical formula of the oxychloride solid electrolyte is xLi2O-(1-y)ZrCl4-yAlCl3, wherein 0 <x≤3,0<y≤1。

[0008] Furthermore, the oxychloride solid electrolyte is composed of an amorphous phase and a crystalline phase, wherein the crystalline phase accounts for ≤20%, the crystal system of the crystalline phase is trigonal and / or monoclinic, and the space group is and / or C2 / m.

[0009] The present invention provides a method for preparing the oxychloride solid electrolyte, comprising the following steps:

[0010] Li2O, ZrCl4 and AlCl3 are mixed and then subjected to high-energy ball milling to obtain an oxychloride solid electrolyte.

[0011] Furthermore, the molar ratio of Li2O, ZrCl4 and AlCl3 is 0.5-2: 0.4-0.9: 0.1-0.6.

[0012] Furthermore, the mixing time is 20 to 40 minutes.

[0013] Furthermore, the ball-to-material ratio of the high-energy ball mill is 10-45:1, the rotation speed of the high-energy ball mill is 150-550 rpm, and the time of the high-energy ball mill is 2-40 hours.

[0014] The present invention also provides an application of the oxychloride solid electrolyte in an all-solid-state lithium battery.

[0015] Beneficial effects of the present invention:

[0016] 1) The highly amorphous xLi2O-(1–y)ZrCl4-yAlCl3 oxychloride solid electrolyte prepared by the present invention has a low Young's modulus (less than 4 GPa, much lower than the Young's modulus of 10-100 GPa of most other solid electrolytes), a high ionic conductivity (higher than 1 mS·cm at 25°C), and a -1 ), no need to use expensive compounds as raw materials, etc.;

[0017] 2) The xLi2O-(1–y)ZrCl4-yAlCl3 oxychloride solid electrolyte prepared by the present invention has an anion framework composed of Zr-O / Cl and / or Al-O / Cl polyhedrons through an ideal O / Cl corner sharing method, with a Young's modulus as low as 1.41 GPa at room temperature and an ionic conductivity as high as 2.55 mS·cm -1 Therefore, xLi2O-(1–y)ZrCl4-yAlCl3 electrolyte and high nickel cathode (LiNi 0.92 Co 0.06 Mn 0.02 O2, abbreviation: scNCM92) high-voltage all-solid-state batteries exhibit excellent electrochemical performance (capacity retention rate of more than 80% after >4000 cycles);

[0018] 3) The synthesis of the xLi2O-(1–y)ZrCl4-yAlCl3 oxychloride solid electrolyte prepared by the present invention does not require expensive raw materials such as Li2S and / or rare earth compounds, and has great cost advantages and good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the X-ray diffraction pattern of 1.0Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 1;

[0020] Figure 2 The electrochemical impedance spectroscopy diagram of 1.0Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 1;

[0021] Figure 3 This is the DC polarization diagram of 1.0Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 1;

[0022] Figure 4 This is the Young's modulus distribution diagram of 1.0Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 1;

[0023] Figure 5 This is the X-ray diffraction pattern of 1.8Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 2;

[0024] Figure 6 This is the electrochemical impedance spectroscopy diagram of 1.8Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 2;

[0025] Figure 7 This is the DC polarization diagram of 1.8Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 2;

[0026] Figure 8 This is the Young's modulus distribution diagram of 1.8Li2O-0.8ZrCl4-0.2AlCl3 prepared in Example 2;

[0027] Fig. 9 This is the X-ray diffraction pattern of 1.0Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 3;

[0028] Fig.10 The electrochemical impedance spectroscopy diagram of 1.0Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 3;

[0029] Fig.11 This is the DC polarization diagram of 1.0Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 3;

[0030] Fig.12 This is the X-ray diffraction pattern of 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4;

[0031] Fig.13 The electrochemical impedance spectroscopy diagram of 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4;

[0032] Fig.14 This is the DC polarization diagram of 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4;

[0033] Fig.15 This is the Young's modulus distribution diagram of 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4;

[0034] Fig.16 The Li-In|Li6PS5Cl-1.4Li2O-0.75ZrCl4-0.25AlCl3|scNCM92 battery assembled with 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4 was charged at 10C (2000mA·g -1 ) Long cycle performance diagram under ) rate;

[0035] Fig.17The Li-In|Li6PS5Cl-1.4Li2O-0.75ZrCl4-0.25AlCl3|scNCM92 battery assembled with 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4 was heated at 0.1C (20mA·g -1 ) long cycle performance under high rate and high active material loading (a) and corresponding charge and discharge curves (b);

[0036] Fig.18 This is the X-ray diffraction pattern of 1.8Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 5;

[0037] Fig.19 The electrochemical impedance spectroscopy diagram of 1.8Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 5;

[0038] Fig. 20 This is the DC polarization diagram of 1.8Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 5;

[0039] Fig.21 This is the X-ray diffraction pattern of 1.0Li2O-0.7ZrCl4-0.3AlCl3 prepared in Example 6;

[0040] Fig. 22 The electrochemical impedance spectroscopy diagram of 1.0Li2O-0.7ZrCl4-0.3AlCl3 prepared in Example 6;

[0041] Fig.23 This is the DC polarization diagram of 1.0Li2O-0.7ZrCl4-0.3AlCl3 prepared in Example 6;

[0042] Fig.24 This is the Young's modulus distribution diagram of 1.0Li2O-0.7ZrCl4-0.3AlCl3 prepared in Example 6;

[0043] Fig.25 This is the X-ray diffraction pattern of 1.0Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 7;

[0044] Fig.26 The electrochemical impedance spectroscopy diagram of 1.0Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 7;

[0045] Fig. 27 This is the DC polarization diagram of 1.0Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 7;

[0046] Fig.28Young's modulus distribution diagram of 1.0Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 7;

[0047] Fig.29 X-ray diffraction pattern of 1.8Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 8;

[0048] Fig.30 Electrochemical impedance diagram of 1.8Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 8;

[0049] Fig.31 DC polarization diagram of 1.8Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 8;

[0050] Fig.32 Young's modulus distribution diagram of 1.8Li2O-0.5ZrCl4-0.5AlCl3 prepared in Example 8. Detailed implementation manners

[0051] The present invention provides an oxychloride solid electrolyte, and the chemical general formula of the oxychloride solid electrolyte is xLi2O-(1-y)ZrCl4-yAlCl3, where 0 < x ≤ 3, 0 < y ≤ 1, preferably 0.5 < x ≤ 2, 0.1 < y ≤ 0.6, and further preferably 1 ≤ x ≤ 1.8, 0.2 ≤ y ≤ 0.5.

[0052] In the present invention, the oxychloride solid electrolyte is composed of an amorphous phase and a crystalline phase, where the proportion of the crystalline phase ≤ 20%, preferably ≤ 15%, and further preferably ≤ 10%; the crystal system of the crystalline phase is trigonal and / or monoclinic; the space group is and / or C2 / m.

[0053] The present invention provides a preparation method of the oxychloride solid electrolyte, including the following steps:

[0054] Mix Li2O, ZrCl4 and AlCl3 and then carry out high-energy ball milling to obtain the oxychloride solid electrolyte.

[0055] In the present invention, the molar ratio of Li2O, ZrCl4 and AlCl3 is 0.5-2:0.4-0.9:0.1-0.6, preferably 0.7-1.9:0.45-0.85:0.15-0.55, and further preferably 1-1.8:0.5-0.8:0.2-0.5.

[0056] In the present invention, the mixing time is 20-40 min, preferably 25-35 min, and further preferably 30 min.

[0057] In the present invention, the ball-to-material ratio of the high-energy ball mill is 10 to 45:1, preferably 15 to 40:1, and more preferably 20 to 25:1; the rotation speed of the high-energy ball mill is 150 to 550 rpm, preferably 250 to 500 rpm, and more preferably 500 rpm; the time of the high-energy ball mill is 2 to 40 h, preferably 5 to 30 h, and more preferably 20 to 30 h.

[0058] The present invention also provides an application of the oxychloride solid electrolyte in an all-solid-state lithium battery.

[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0060] Example 1

[0061] In an argon-protected glove box (water and oxygen content less than 0.01ppm), Li2O, ZrCl4 and AlCl3 with a molar ratio of 1:0.8:0.2 were mixed in an agate mortar for 30 minutes, and then transferred to an 80mL zirconia ball milling jar after mixing. The diameter of the zirconia grinding ball was 5mm, and the ball-to-material mass ratio was 20:1. High-energy ball milling was performed at a speed of 500rpm in a high-energy ball mill Pulverisette7 of German Flying Chip Company for 30 hours to obtain a 1.0Li2O-0.8ZrCl4-0.2AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20%, wherein the crystal phase is monoclinic and the space group is C2 / m

[0062] The X-ray diffraction diagram, electrochemical impedance diagram, DC polarization diagram and Young's modulus distribution diagram of the oxychloride solid electrolyte prepared in Example 1 were tested, and the test results were as follows: Figures 1 to 4 As shown. Figures 1 to 4 It can be seen that the room temperature ionic conductivity (σ i ) is 1.98mS·cm -1 , room temperature electronic conductivity (σ e ) is 1.72×10 -9 S cm -1 The fact that ionic conductivity is six orders of magnitude higher than electronic conductivity proves that 1.0Li2O-0.8ZrCl4-0.2AlCl3 is a pure ionic conductor that can be used as a solid-state battery. At the same time, the Young's modulus of 1.0Li2O-0.8ZrCl4-0.2AlCl3 is 2.47GPa, indicating that the electrolyte has good mechanical deformation ability.

[0063] Example 2

[0064] In Example 2, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.8:0.8:0.2, and the other conditions are the same as in Example 1, and a 1.8Li2O-0.8ZrCl4-0.2AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20% is obtained, wherein the crystal phase is monoclinic and the space group is C2 / m.

[0065] The X-ray diffraction pattern, electrochemical impedance diagram, DC polarization diagram and Young's modulus distribution diagram of the oxychloride solid electrolyte prepared in Example 2 were tested, and the test results were as follows: Figures 5 to 8 As shown. Figures 5 to 8 It can be seen that the room temperature ionic conductivity (σ i ) is 0.624mS·cm -1 , room temperature electronic conductivity (σ e ) is 5.61×10 -10 S cm -1 The fact that ionic conductivity is six orders of magnitude higher than electronic conductivity proves that 1.8Li2O-0.8ZrCl4-0.2AlCl3 is a pure ionic conductor that can be used as a solid-state battery. At the same time, the Young's modulus of 1.8Li2O-0.8ZrCl4-0.2AlCl3 is 3.98GPa, indicating that the electrolyte has good mechanical deformation ability.

[0066] Example 3

[0067] In Example 3, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.0:0.75:0.25, and the other conditions are the same as those in Example 1, to obtain a 1.0Li2O-0.75ZrCl4-0.25AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20%, wherein the crystal phase is a trigonal system and the space group is

[0068] The X-ray diffraction pattern, electrochemical impedance diagram and DC polarization diagram of the oxychloride solid electrolyte prepared in Example 3 were tested, and the test results were as follows: Figures 9-11 As shown. Figures 9-11 It can be seen that the room temperature ionic conductivity (σ i ) is 2.01mS·cm -1 , room temperature electronic conductivity (σ e ) is 2.7×10 -9 S cm -1 , the fact that the ionic conductivity is five orders of magnitude higher than the electronic conductivity proves that 1.0Li2O-0.75ZrCl4-0.25AlCl3 is a pure ionic conductor that can be used as a solid-state battery.

[0069] Example 4

[0070] In Example 4, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.4:0.75:0.25, and the other conditions are the same as those in Example 1, to obtain a 1.4Li2O-0.75ZrCl4-0.25AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20%, wherein the crystal phase is a coexistence of trigonal and monoclinic systems, and the space group is and C2 / m.

[0071] The X-ray diffraction pattern, electrochemical impedance diagram and DC polarization diagram of the oxychloride solid electrolyte prepared in Example 4 were tested, and the test results were as follows: Figures 12 to 15 As shown. Figures 12 to 15 It can be seen that the room temperature ionic conductivity (σ i ) is 2.55mS·cm -1 , room temperature electronic conductivity (σ e ) is 3.09×10 -9 S cm -1 The fact that ionic conductivity is five orders of magnitude higher than electronic conductivity proves that 1.4Li2O-0.75ZrCl4-0.25AlCl3 is a pure ionic conductor that can be used as a solid-state battery. At the same time, the Young's modulus of 1.4Li2O-0.75ZrCl4-0.25AlCl3 is 1.41GPa, indicating that the electrolyte has good mechanical deformation ability.

[0072] In an argon-protected glove box (water and oxygen content less than 0.01ppm), the all-solid-state lithium battery was assembled. The composite positive electrode is made of single crystal LiNi 0.92 Co 0.06 Mn 0.02 O2 and 1.4Li2O-0.75ZrCl4-0.25AlCl3 prepared in Example 4 were mixed in a mass ratio of 75:25 using a vortex mixer at 1500rpm for 15 minutes. The steps of assembling the all-solid-state lithium battery are as follows: first, 25mg of 1.4Li2O-0.75ZrCl4-0.25AlCl3 powder was cold-pressed into a PEEK mold with a diameter of 10mm at a pressure of 150MPa and the pressure was maintained for 1 minute; then, 5-30mgcm -2The loaded composite positive electrode is dispersed on one side of the 1.4Li2O-0.75ZrCl4-0.25AlCl3 layer and maintained at a pressure of 300MPa for 5 minutes; secondly, in order to avoid the side reaction between 1.4Li2O-0.75ZrCl4-0.25AlCl3 and the negative electrode, 35mg of sulfide Li6PS5Cl powder is evenly dispersed on the other side of the 1.4Li2O-0.75ZrCl4-0.25AlCl3 layer, and then maintained at a pressure of 150MPa for 1 minute; finally, the negative electrode Li-In is compacted on the Li6PS5Cl side, and an external pressure of 190MPa is applied to the entire battery. The assembled all-solid-state lithium battery was tested, and the test results are as follows Figures 16-17 As shown. Figures 16-17 It can be seen that at 5-6 mg cm -2 Under the conventional positive electrode active material loading, the all-solid-state battery can -1 ) After 4208 cycles, the capacity retention rate is as high as 80%; when the positive electrode active material loading exceeds 20 mg cm -2 When the all-solid-state battery is at 0.1C (20mA·g -1 ) After 20 cycles, the capacity is as high as 4.22 mAh cm -2 (Capacity retention rate 98.18%).

[0073] Example 5

[0074] In Example 5, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.8:0.75:0.25, and the other conditions are the same as in Example 1, and a 1.8Li2O-0.75ZrCl4-0.25AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20% is obtained, wherein the crystal phase is monoclinic and the space group is C2 / m.

[0075] The X-ray diffraction pattern, electrochemical impedance diagram and DC polarization diagram of the oxychloride solid electrolyte prepared in Example 5 were tested, and the test results were as follows: Figures 18 to 20 As shown. Figures 18 to 20 It can be seen that the room temperature ionic conductivity (σ i ) is 0.733mS·cm -1 , room temperature electronic conductivity (σ e ) is 1.22×10 -9 S cm -1 The fact that the ionic conductivity is five orders of magnitude higher than the electronic conductivity proves that 1.8Li2O-0.75ZrCl4-0.25AlCl3 is a pure ionic conductor that can be used as a solid-state battery.

[0076] Example 6

[0077] In Example 6, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.0:0.7:0.3, and the other conditions are the same as those in Example 1, to obtain a 1.0Li2O-0.7ZrCl4-0.3AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20%, wherein the crystal phase is a trigonal system and the space group is

[0078] The X-ray diffraction pattern, electrochemical impedance diagram and DC polarization diagram of the oxychloride solid electrolyte prepared in Example 6 were tested, and the test results were as follows: Figures 21 to 24 As shown. Figures 21 to 24 It can be seen that the room temperature ionic conductivity (σ i ) is 1.74mS·cm -1 , room temperature electronic conductivity (σ e ) is 3.27×10 -9 S cm -1 The fact that ionic conductivity is five orders of magnitude higher than electronic conductivity proves that 1.0Li2O-0.7ZrCl4-0.3AlCl3 is a pure ionic conductor that can be used as a solid-state battery. At the same time, the Young's modulus of 1.0Li2O-0.7ZrCl4-0.3AlCl3 is 3.65GPa, indicating that the electrolyte has good mechanical deformation ability.

[0079] Example 7

[0080] In Example 7, the molar ratio of Li2O, ZrCl4 and AlCl3 is 1.0:0.5:0.5, and the other conditions are the same as those in Example 1, and a 1.0Li2O-0.5ZrCl4-0.5AlCl3 oxychloride solid electrolyte with a crystal phase ratio of ≤20% is obtained, wherein the crystal phase is a trigonal system and the space group is

[0081] The X-ray diffraction pattern, electrochemical impedance diagram and DC polarization diagram of the oxychloride solid electrolyte prepared in Example 7 were tested, and the test results were as follows: Figures 25 to 28 As shown. Figures 25 to 28 It can be seen that the room temperature ionic conductivity (σ i ) is 0.846mS·cm -1 , room temperature electronic conductivity (σ e ) is 4.06×10 -9 S cm -1, the fact that the ionic conductivity is five orders of magnitude higher than the electronic conductivity proves that 1.0Li2O-0.5ZrCl4-0.5AlCl3 can be used as a pure ionic conductor for solid-state batteries. At the same time, the Young's modulus of 1.0Li2O-0.5ZrCl4-0.5AlCl3 is 3.01 GPa, indicating that this electrolyte has good mechanical deformation ability.

[0082] Example 8

[0083] In Example 8, the molar ratio of Li2O, ZrCl4, and AlCl3 is 1.8:0.5:0.5, and other conditions are the same as in Example 1, obtaining an oxychloride solid electrolyte of 1.8Li2O-0.5ZrCl4-0.5AlCl3 with a crystalline phase proportion ≤20%, where the crystalline phase is monoclinic and the space group is C2 / m.

[0084] The X-ray diffraction pattern, electrochemical impedance pattern, and DC polarization pattern of the oxychloride solid electrolyte prepared in Example 8 were tested, and the test results are shown as Figures 29 to 32 follows. It can be seen from Figures 29 to 32 that the room-temperature ionic conductivity (σ i ) of the oxychloride solid electrolyte prepared in Example 8 is 0.367 mS·cm -1 , and the room-temperature electronic conductivity (σ e ) is 1.68×10 -9 S·cm -1 . The fact that the ionic conductivity is five orders of magnitude higher than the electronic conductivity proves that 1.8Li2O-0.5ZrCl4-0.5AlCl3 can be used as a pure ionic conductor for solid-state batteries. At the same time, the Young's modulus of 1.8Li2O-0.5ZrCl4-0.5AlCl3 is 3.84 GPa, indicating that this electrolyte has good mechanical deformation ability.

[0085] From the above examples, it can be seen that the present invention provides an oxychloride solid electrolyte, its preparation method and application. The chemical general formula of the oxychloride solid electrolyte is xLi2O-(1–y)ZrCl4-yAlCl3, where 0<x≤3 and 0<y≤1. Compared with other solid electrolytes such as sulfides, halides, and oxides (whose Young's moduli mostly exceed 20 GPa, even higher than 100 GPa), the oxychloride solid electrolyte in the present invention has a lower Young's modulus (not higher than 4 GPa); the all-solid-state lithium battery assembled using the oxychloride solid electrolyte of the present invention has excellent areal capacity and long cycle stability.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An oxychloride solid electrolyte, characterized in that: The chemical formula of the oxychloride solid electrolyte is xLi2O-(1-y)ZrCl4-yAlCl3, where 0 <x≤3,0<y≤1。 2. The oxychloride solid electrolyte according to claim 1, characterized in that: The oxychloride solid electrolyte is composed of an amorphous phase and a crystalline phase, wherein the crystalline phase accounts for ≤20%, the crystal system of the crystalline phase is trigonal and / or monoclinic, and the space group is and / or C2 / m.

3. A method for preparing the oxychloride solid electrolyte according to claim 1 or 2, characterized in that: The following steps are involved: Li2O, ZrCl4 and AlCl3 are mixed and then subjected to high-energy ball milling to obtain an oxychloride solid electrolyte.

4. The method for preparing the oxychloride solid electrolyte according to claim 3, characterized in that: The molar ratio of Li2O, ZrCl4 and AlCl3 is 0.5-2: 0.4-0.9: 0.1-0.

6.

5. The method for preparing the oxychloride solid electrolyte according to claim 4, characterized in that: The mixing time is 20 to 40 minutes.

6. The method for preparing the oxychloride solid electrolyte according to claim 4 or 5, characterized in that: The ball-to-material ratio of the high-energy ball mill is 10-45:1, the rotation speed of the high-energy ball mill is 150-550 rpm, and the time of the high-energy ball mill is 2-40 hours.

7. Use of the oxychloride solid electrolyte according to claim 1 or 2 in an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Inorganic chloride solid electrolyte material and preparation method and application thereof

    CN112591793A

  • Solid electrolyte material and application thereof

    CN114614081A

  • Halide all-solid-state battery material and preparation method and application thereof

    CN115275331A

  • Oxygen-containing chloride solid electrolyte and preparation method and application thereof

    CN115842157A

  • Oxidation halide solid electrolyte and preparation method and application thereof

    CN118336096A

Cited By

  • Zirconium-based solid electrolyte and preparation method and application thereof

    CN121769215A

  • Polyanion zirconium-based solid electrolyte as well as preparation method and application thereof

    CN121769216A